Implementing a standardised annual programme review process in a third-level institution. Issue 3 (3rd July 2017) - Wickham, Sheelagh; Brady, Malcolm; Ingle, Sarah; McMullan, Caroline; Nic Giolla Mhichíl, Mairéad; Walshe, Ray
Abstract : Purpose: Ideally, quality should be, and is, an integral element of education, yet capturing and articulating quality is not simple. Programme quality reviews in third-level education can demonstrate quality and identify areas for improvement, offering many potential benefits. However, details on the process of quality programme review are limited in the literature. This study aims to report on the introduction of a standardised programme review process in one university. Design/methodology/approach: Using a standardised template, the annual programme review (APR) process captured student voice, external examiner reports, statistical data and action/s since the previous review. Following completion of programme reviews across the university, the APR process was itself evaluated using questionnaires and focus groups. Findings: Findings showed that the programme chairs understood the rationale for the review, welcomed the standardised format and felt the information could inform future programme planning. However, in the focus group, issues arose about the timing, ownership and possible alternate use of the data collected in the course of the review. Research limitations/implications: This case study demonstrates the experience of APR in a single third-level institution, therefore, limiting generalisability. Practical implications: APR offers a comprehensive record of the programme that can be carried out with efficacy and efficiency. The study illustrates one institution's experience, and this may assist others in using similar quality evaluation tools. Using APR allows quality to be measured, articulated and improved. Social implications: Using APR allows quality, or its lack to be to be measured, articulated and improved in the delivery of education at a third-level institution. Originality/value: This study demonstrates the experience of the introduction of an APR process in one higher education institute. Programme review is an important and essential part of academia in the 21st century. At third level, quality assurance is, or should be, a central part of academic programmes and delivery. The review of the first implementation has provided valuable information that will inform future programme review processes. Academic programmes grow, evolve and need to be reviewed regularly. It is hoped that the information reported here will aid others developing academic review procedures.